Digital Community Empowerment for Competitive Farmers in Marketing Farmer Products in Sigi Regency, Central Sulawesi, Indonesia - Mohammad Yasin; Idham (International Journal of Science and Environment (IJSE), 2026)
This research examines digital empowerment and farmer competitiveness in Sigi Regency. The goal is to understand the digital empowerment process, the socio-cultural significance of farmers' digital activities, and their contribution to competitiveness. The approach used is qualitative interpretive with a cyber-phenomenology paradigm through photo elicitation and MDAP methods. The results indicate that digital empowerment encompasses economic, social, and cultural dimensions.